RAISE: a simple and novel method of generating random insertion and deletion mutations - Fujii, Ryota (Oxford University Press, 2006)
Although proteins may be artificially improved by random insertion and deletion mutagenesis methods, these procedures are technically difficult, and the mutations introduced are no more variable than those introduced by the introduction of random point mutations. We describe here a three-step method called RAISE, which is based on gene shuffling and can introduce a wide variety of insertions, deletions and substitutions. To test the efficacy of this method, we used it to mutate TEM β-lactamase to generate improved antibiotic resistance. Some unique insertion or deletion mutations were observed in the improved mutants, some of which caused higher activities than point mutations. Our findings indicate that the RAISE method can yield unique mutants and may be a powerful technique of protein engineering.